Decision support system funding on the website of Dana Syariah using the Simple Additive Weighting method - Tansa Wiguna; Aulia Putri Restu Rahayu; Soetam Rizky Wicaksono (Borobudur Informatics Review, 2021)
Dana Syariah is a Sharia-based Fintech P2P Financing company that is licensed and supervised by the Financial Services Authority (OJK). Focusing on property funding and registered since June 8 2018. From June 2018 – March 2021, Dana Syariah provides financing with a nominal value of approximately Rp. 1.28 trillion and around 62 thousand active lenders provide loans that are used by 1000 property project units. To get results as needed in choosing funding, a decision support is needed using the SAW method. The basic concept of the SAW method is to search for a weighted sum based on a rating for each available alternative in all attributes. The SAW method is known by two attribute terms, namely the benefit criteria and the cost criteria. The difference between these two criteria is part of the selection of criteria when making decisions. The criteria applied include: (1) Project Tenor/Duration (2) Annual Returns/Results (3) Collateral (4) Project Owner. After determining the criteria and weighting, then you can determine the scale with the provisions of the assessment for each criterion. The SAW method can be scientifically proven and can be used in logic to support decision making. In procurement or funding on the Dana Syariah website, an analysis of several available funding programs is carried out. The results of this study, based on 6 objects, there are 3 objects that have a similar rating with the first recommendation ranking.